Isolation and Characterization of Alfalfa-Nodulating Rhizobia Present in Acidic Soils of Central Argentina and Uruguay - Del Papa, María Florencia (1999)
We describe the isolation and characterization of alfalfa-nodulating rhizobia from acid soils of different locations in Central Argentina and Uruguay. A collection of 465 isolates was assembled, and the rhizobia were characterized for acid tolerance. Growth tests revealed the existence of 15 acid-tolerant (AT) isolates which were able to grow at pH 5.0 and formed nodules in alfalfa with a low rate of nitrogen fixation. Analysis of those isolates, including partial sequencing of the genes encoding 16S rRNA and genomic PCR-fingerprinting with MBOREP1 and BOXC1 primers, demonstrated that the new isolates share a genetic background closely related to that of the previously reported Rhizobium sp. Or191 recovered from an acid soil in Oregon (B. D. Eardly, J. P. Young, and R. K. Selander, Appl. Environ. Microbiol. 58:1809–1815, 1992). Growth curves, melanin production, temperature tolerance, and megaplasmid profiles of the AT isolates were all coincident with these characteristics in strain Or191. In addition to the ability of all of these strains to nodulate alfalfa (Medicago sativa) inefficiently, the AT isolates also nodulated the common bean and Leucaena leucocephala, showing an extended host range for nodulation of legumes. In alfalfa, the time course of nodule formation by the AT isolate LPU 83 showed a continued nodulation restricted to the emerging secondary roots, which was probably related to the low rate of nitrogen fixation by the largely ineffective nodules. Results demonstrate the complexity of the rhizobial populations present in the acidic soils represented by a main group of N2-fixing rhizobia and a second group of ineffective and less-predominant isolates related to the AT strain Or191.